Darryl Jones, Sleeping with the Lights On: The Unsettling Story of Horror. (31st December 2018) - Clasen, Mathias
Abstract : Darryl Jones, Sleeping with the Lights On: The Unsettling Story of Horror (Oxford: Oxford University Press, 2018), xii + 181 pp. £10.99/$16.95. ISBN 978-0-19882-648-4.